Mechanical versus manual chest compression CPR under ground ambulance transport conditions. (March 2013) - Fox, Julia; Fiechter, René; Gerstl, Peter; Url, Alfons; Wagner, Heinz; Lüscher, Thomas F.; Eriksson, Urs; Wyss, Christophe A.
<x xml:space="preserve">Abstract</x> Background: Novel mechanical chest compression devices offer the possibility to transport cardiac arrest patients with ongoing CPR and might shorten significantly the time delay to post-resuscitation care. Methods: We simulated an eight-minute cardiac resuscitation situation during ambulance transport using CPR training manikins. We compared teams consisting of two experienced resuscitators with the performance of a mechanical chest compression device (LUCAS). Results: CPR-performance by two experienced resuscitators demonstrated ambivalent results. Whereas mean compression rate was within the recommended range (103/min, 95% CI: 93–113/min), mean compression depth was closely below the actually recommended compression depth of >5 cm (49.7 mm, 95% CI: 46.1–53.3mm). Nevertheless, only a mean of two thirds (67%) of all compressions were classified as manually correct (defined as sternal compression depth >5 cm). In contrast, the LUCAS device showed a constant and reliable CPR performance (99.96% correctly applied chest compressions correctly applied within the device programmed parameters, P = 0.0162) with almost no variance between the different sequences. Conclusion: The LUCAS CPR device represents a reliable alternative to manual CPR in a moving ambulance vehicle during emergency evacuation. Furthermore, it needs less human resources and is safer for the EMS personnel.